Collection and delivery points in the last mile of cargo transportation: Sustainability benefits and challenges - Gustavo Henrique Freitas Matinha; Carlos Eduardo Sanches de Andrade; Cintia Isabel de Campos (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
The present work aims to analyze sustainability aspects related to the use of lockers, collection points, and other forms of fixed points, by transporters and consumers, in the last mile of cargo transportation, as an alternative to home delivery. For this purpose, a literature review was performed. Three distinct platforms were researched using strings in three different languages, Portuguese, English, and Spanish. From these databases, 31 articles were selected, all of them according to the subject studied. The papers highlighted the advantages of this type of delivery, embracing not only the environmental gains but also the economic and social ones, such as the reduction of traffic congestion and an overall lower operational cost. Reduction of greenhouse gas emissions and atmospheric pollutants are shown in 23 papers; lower operating costs for transporters in 26 papers, while 23 articles address congestion reduction. The biggest challenge identified is the distance traveled by clients/pedestrians, cited 21 times.